Imaging Nicotine- and Amphetamine-Induced Dopamine Release in Rhesus Monkeys with [(11)C]PHNO vs [(11)C]raclopride PET - Gallezot, Jean-Dominique (Nature Publishing Group, 2014)
The radiotracer [(11)C]PHNO may have advantages over other dopamine (DA) D(2)/D(3) receptor ligands because, as an agonist, it measures high-affinity, functionally active D(2)/D(3) receptors, whereas the traditionally used radiotracer [(11)C]raclopride measures both high- and low-affinity receptors. Our aim was to take advantage of the strength of [(11)C]PHNO for measuring the small DA signal induced by nicotine, which has been difficult to measure in preclinical and clinical neuroimaging studies. Nicotine- and amphetamine-induced DA release in non-human primates was measured with [(11)C]PHNO and [(11)C]raclopride positron emission tomography (PET) imaging. Seven adult rhesus monkeys were imaged on a FOCUS 220 PET scanner after injection of a bolus of [(11)C]PHNO or [(11)C]raclopride in three conditions: baseline; preinjection of nicotine (0.1 mg/kg bolus+0.08 mg/kg infusion over 30 min); preinjection of amphetamine (0.4 mg/kg, 5 min before radiotracer injection). DA release was measured as change in binding potential (BP(ND)). Nicotine significantly decreased BP(ND) in the caudate (7±8%), the nucleus accumbens (10±7%), and in the globus pallidus (13±15%) measured with [(11)C]PHNO, but did not significantly decrease BP(ND) in the putamen or the substantia nigra or in any region when measured with [(11)C]raclopride. Amphetamine significantly reduced BP(ND) in all regions with both radiotracers. In the striatum, larger amphetamine-induced changes were detected with [(11)C]PHNO compared with [(11)C]raclopride (52–64% vs 33–35%, respectively). We confirmed that [(11)C]PHNO is more sensitive than [(11)C]raclopride to nicotine- and amphetamine-induced DA release. [(11)C]PHNO PET may be more sensitive to measuring tobacco smoking-induced DA release in human tobacco smokers.